2014
DOI: 10.5152/tjar.2014.24892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of BIS Usage on Anaesthetic Agent Consumption, Haemodynamics and Recovery Time in Supratentorial Mass Surgery

Abstract: Although using BIS monitoring to evaluate depth of anaesthesia does not bring much benefit versus the use of haemodynamic parameters, it may be beneficial for selected surgeries such as awake craniotomy, for patients with a history of awareness and in haemodynamically unstable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Karaca et al found that time to spontaneous breathing was shorter and time to eye opening was longer when BIS was used compared to the control group, although these differences were not statistically significant [ 18 ]. They concluded that it was difficult to say whether there was a significant difference in terms of total cost when BIS monitoring was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karaca et al found that time to spontaneous breathing was shorter and time to eye opening was longer when BIS was used compared to the control group, although these differences were not statistically significant [ 18 ]. They concluded that it was difficult to say whether there was a significant difference in terms of total cost when BIS monitoring was used.…”
Section: Discussionmentioning
confidence: 99%
“…With total intravenous anesthesia techniques the need for disposables (syringe, extension tube for infusion set, valve) increases total cost [ 14 , 15 ]. Some studies compared the cost of anesthesia with BIS vs. hemodynamic monitoring [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…e bispectral index (BIS), derived from electroencephalogram, is the most commonly used and accepted monitor for assessing the level of sedation and depth of anesthesia [10,[12][13][14][15]. BIS predicts movement in response to surgery and detects consciousness under different anesthetic drugs [15][16][17][18]. It is also a tool that may reduce the incidence of unexpected recall [10,12,13,18].…”
Section: Introductionmentioning
confidence: 99%